2016
DOI: 10.1038/ejhg.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of KREMEN1, a modulator of Wnt signaling, is responsible for ectodermal dysplasia including oligodontia in Palestinian families

Abstract: Tooth development is controlled by the same processes that regulate formation of other ectodermal structures. Mutations in the genes underlying these processes may cause ectodermal dysplasia, including severe absence of primary or permanent teeth. Four consanguineous Palestinian families presented with oligodontia and hair and skin features of ectodermal dysplasia. Appearance of ectodermal dysplasia was consistent with autosomal recessive inheritance. Exome sequencing followed by genotyping of 56 informative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Comparing our patients with the Palestinian patients, the absence of permanent upper lateral incisors and lower anterior teeth, and presence of upper central incisors, were found in all seven patients. 1 This aberrant dental pattern could be a pathognomonic feature of KREMEN1 mutations. More individuals with KREMEN1 mutations are needed to substantiate this observation.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Comparing our patients with the Palestinian patients, the absence of permanent upper lateral incisors and lower anterior teeth, and presence of upper central incisors, were found in all seven patients. 1 This aberrant dental pattern could be a pathognomonic feature of KREMEN1 mutations. More individuals with KREMEN1 mutations are needed to substantiate this observation.…”
mentioning
confidence: 98%
“…Dear Editor , Ectodermal dysplasia (ED) is a heterogeneous group of disorders caused by mutations in at least 13 genes. Recently, a study reported Palestinian patients with ED from consanguineous families with a homozygous mutation in KREMEN1 and proposed it to be a causative gene for the autosomal recessive ED 13, hair/tooth type (ECTD13; OMIM 617392) …”
mentioning
confidence: 99%
See 3 more Smart Citations